If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3+5t=6t
We move all terms to the left:
-3+5t-(6t)=0
We add all the numbers together, and all the variables
-1t-3=0
We move all terms containing t to the left, all other terms to the right
-t=3
t=3/-1
t=-3
| 4*x/5=-16 | | 9x-40=23 | | 4(2x-4)=-6 | | 30+10x+20=90 | | 50+5x+x=180 | | x+391/4=180 | | 17m–9=5 | | x+x+x+32=156-34 | | 9g-3g-1=17 | | 2(7x+4)-10=-44 | | 4g-5=-g | | c/28=3 | | -7-4=4y*(8-6)-64 | | 24=1/3c | | 7-4=4y*(8-6)-64 | | 10x+18=64x | | 7(2l+10)=196 | | -1/3(f+8)=13 | | 3(1+15n)−17n=−361 | | 12x-5=8-25 | | 5u=3+8u | | 4(3x-1)+5=61 | | 4(3n+5)=60 | | 1/2+x=8/15 | | 1+2(q-2)=4(q+2)-5 | | 7*b/4=-49 | | -5(n+8)=-10 | | 31=y/4+8 | | y+0,2(3-2y)=0,5(5y+2)-8 | | Y=15.5x+10 | | -12(4-x)=108 | | 16+y=37 |